Biological and Pharmacological Properties of Myrtenol: A Review - Mrabti, Hanae N.; Jaouadi, Imane; Zeouk, Ikrame; Ghchime, Rokia; El Menyiy, Naoual; El Omari, Nasreddine; Balahbib, Abdelaali; Al-Mijalli, Samiah H.; Abdallah, Emad M.; El-Shazly, Mohamed; Zengin, Gokhan; Bouyahya, Abdelhakim (Current Pharmaceutical Design, 2023)
Myrtenol (C10H16O) is a volatile compound belonging to the terpenoid family of monocyclic monoterpenes. It is one of the essential oils constituents of several aromatic plants, including the genera Myrtus, Tanacetum, Artemisia, Hyssopus, and Rhodiola. The oxidation of α-pinene can produce it. Several reports demonstrated the pharmacological properties of myrtenol, including its antioxidant, antibacterial, antifungal, antidiabetic, anxiolytic, and gastroprotective activities. In this review, we discussed and highlighted in depth the pharmacological activities, cellular and molecular, providing insight into the mechanisms of myrtenol. In light of this finding, the interesting biological activities and abundance of myrtenol in nature suggests its potential applications in medicinal settings in the fight against various diseases.
Keywords: pharmacodynamic